2017
DOI: 10.1371/journal.pone.0174306
|View full text |Cite
|
Sign up to set email alerts
|

Nucleolar asymmetry and the importance of septin integrity upon cell cycle arrest

Abstract: Cell cycle arrest can be imposed by inactivating the anaphase promoting complex (APC). In S. cerevisiae this arrest has been reported to stabilize a metaphase-like intermediate in which the nuclear envelope spans the bud neck, while chromatin repeatedly translocates between the mother and bud domains. The present investigation was undertaken to learn how other features of nuclear organization are affected upon depletion of the APC activator, Cdc20. We observe that the spindle pole bodies and the spindle repeat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 89 publications
0
6
0
Order By: Relevance
“…[22][23][24] Nucleolar markers remain in the mother domain in arrested cells (Figure 1D). 10 Moreover, especially when chromatin (Htb2-mRFP) is in the bud, rDNA and Hmo1 form an elongated filament in the mother domain (Figure 1E), whose length appears comparable to the length of rDNA in cycling cells. 25 Histones (Htb2-mRFP) can be detected along the gnarled Hmo1-GFPpositive filament and occasionally highlights the end of the filament, presumably near the right telomere of chromosome XII (Figures 1A and 1F).…”
Section: The Rdna Axis Is Colinear With Hmo1mentioning
confidence: 92%
See 1 more Smart Citation
“…[22][23][24] Nucleolar markers remain in the mother domain in arrested cells (Figure 1D). 10 Moreover, especially when chromatin (Htb2-mRFP) is in the bud, rDNA and Hmo1 form an elongated filament in the mother domain (Figure 1E), whose length appears comparable to the length of rDNA in cycling cells. 25 Histones (Htb2-mRFP) can be detected along the gnarled Hmo1-GFPpositive filament and occasionally highlights the end of the filament, presumably near the right telomere of chromosome XII (Figures 1A and 1F).…”
Section: The Rdna Axis Is Colinear With Hmo1mentioning
confidence: 92%
“…Correspondingly, cotranscriptional events endow particles with surfaces that are densely covered with AFs. As post-transcriptional steps in subunit genesis entail 10 For all panels, B, bud; M, mother. (E) Projected image of arrested cells that express the histone, Htb2-mRFP, and Hmo1-GFP.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, in these nuclear relationships in the PPI networks of septins, we highlighted links between chromatin partners and septins, coupled with links to splicing molecules. Chromatin has already been described as being link to splicing regulation (de Almeida and Carmo-Fonseca, 2014) and the importance of septin integrity at cell cycle arrest has recently been connected to nucleolar asymmetry (Rai et al, 2017). In this network, we showed that through their partner relationships, septins could participate in the interplay between the spliceosome and chromatin in the nuclear part of cells.…”
Section: Iv-mentioning
confidence: 56%
“…The red bulk chromatin - which transits between mother and bud ( Palmer et al., 1989 ) - can be found on one or the other side of the bud neck or stretching across the bud neck. The nucleolus (labeled by Gar1-GFP) remains in the mother domain, as we have discussed elsewhere ( Rai et al., 2017 , Tartakoff et al., 2021 ). The same approach can be used to monitor the distribution of single proteins or of other organelles.…”
Section: Expected Outcomesmentioning
confidence: 88%
“…For complete details on the use and execution of this protocol, please refer to Tartakoff et al. (2021) , Rai et al. (2017) , and Zapanta Rinonos et al.…”
mentioning
confidence: 99%